Preservation of root cementum: a comparative evaluation of power‐driven versus hand instruments. Issue 2 (16th November 2016) - Bozbay, E; Dominici, F; Gokbuget, AY; Cintan, S; Guida, L; Aydin, MS; Mariotti, A; Pilloni, A
Abstract: Objectives: The purpose of this study was to evaluate the effects of three distinct periodontal treatment methods in comparison with hand instrumentation on residual cementum of periodontal diseased teeth. Cementum can influence the activities of periodontal cells and may play an important regulatory role in periodontal treatment. The ideal method for periodontal therapy involves removal of biofilm, calculus and endotoxin while preserving root cementum. Material and methods: Forty‐eight caries free, single‐rooted teeth in patients diagnosed with severe chronic periodontitis were treated using four different methods prior to extraction. The teeth were instrumented subgingivally at one approximal site either by hand curettes (HC), piezoelectric ultrasonic scalers (U), piezoelectric ultrasonic scalers following air polishing (U + AP) or air polishing (AP) alone. Following extraction of teeth, instrumented and non‐instrumented sites were analysed with a dissecting microscope and SEM for measurement of the amount of and surface characteristics of residual cementum. Results: The percentage of coronal cementum remaining following subgingival instrumentation was 84% for U, 80% for U + AP, 94% for AP and 65% for HC. Although subgingival instrumentation of apical portions of the cementum demonstrated 6% less retained cementum in comparison with coronal portions, the amount of retained cementum with AP was still significantly greater than with HC. SEM results found the smoothest root surfaces were produced by the HC followed by the AP, while root surfaces instrumented by U or U + AP presented grooves and scratches. Conclusions: This study demonstrated that AP was superior to U devices in preserving cementum, whereas HC were the most effective instruments in removing cementum.